2014
DOI: 10.1039/c3ra47233g
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-controlled reversible exfoliation-stacking of titanate nanosheets in an aqueous solution containing tetraalkylammonium ions

Abstract: Exfoliation and stacking of titanate nanosheets dispersed in aqueous solutions containing tetraalkylammonium ions can be reversibly controlled by adjusting the solution temperature as a tunable physical parameter. That is, the transparent colloidal solution of exfoliated titanates is clouded on the basis of spontaneous staking of multiple nanosheets when heated at a certain temperature, and cooling of the clouded solution causes regeneration of the original exfoliated state. This cycle repeatedly and rapidly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Our previous paper demonstrated that the crystal structure of TNS produced by the hydrolysis of TTIP is akin to the tetratitanate (Ti 4 O 9 2À ). 19 In addition, The diffraction line assigned to the (200) plane of tetratitanate intercalated with TBA + counter ions appeared in the XRD pattern of the solid aer drying the colloidal solution (Fig. 1b).…”
Section: Resultsmentioning
confidence: 96%
“…Our previous paper demonstrated that the crystal structure of TNS produced by the hydrolysis of TTIP is akin to the tetratitanate (Ti 4 O 9 2À ). 19 In addition, The diffraction line assigned to the (200) plane of tetratitanate intercalated with TBA + counter ions appeared in the XRD pattern of the solid aer drying the colloidal solution (Fig. 1b).…”
Section: Resultsmentioning
confidence: 96%
“…1b. According to literatures, 24,25 the colloidal particles prepared by the present hydrolysis technique have a crystal structure consisting of tetratitanate (Ti 4 O 9…”
Section: Resultsmentioning
confidence: 94%
“…Solid components in the solution had tiny dimensions less than 10 nm with a narrow distribution, and a mean hydrodynamic diameter gradually increased with increasing Ce content (Figure 1b). Our previous papers demonstrated that the crystal structure of TNS produced by the hydrolysis of TTIP is akin to tetratitanate (Ti 4 O 9 2− ) 21 and that the colloidal particle seems to be a tiny stack assembled with several nanosheets (average stack number <5). 22 In fact, the diffraction line assigned to (200) plane of tetratitanate intercalated with bulky TBA + counterions appeared in the XRD pattern of solid after drying the colloidal solutions irrespective of Ce content (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%